Is Contrast Medium Osmolality a Causal Factor for Contrast-Induced Nephropathy?. (31st March 2014) - Bucher, Andreas M.; De Cecco, Carlo N.; Schoepf, U. Joseph; Meinel, Felix G.; Krazinski, Aleksander W.; Spearman, James V.; McQuiston, Andrew D.; Wang, Rui; Bucher, Judith; Vogl, Thomas J.; Katzberg, Richard W.
Abstract : The exact pathophysiology of contrast-induced nephropathy (CIN) is not fully clarified, yet the osmotic characteristics of contrast media (CM) have been a significant focus in many investigations of CIN. Osmotic effects of CM specific to the kidney include transient decreases in blood flow, filtration fraction, and glomerular filtration rate. Potentially significant secondary effects include an osmotically induced diuresis with a concomitant dehydrating effect. Clinical experiences that have compared the occurrence of CIN between the various classes of CM based on osmolality have suggested a much less than anticipated advantage, if any, with a lower osmolality. Recent animal experiments actually suggest that induction of a mild osmotic diuresis in association with iso-osmolar agents tends to offset potentially deleterious renal effects of high viscosity-mediated intratubular CM stagnation.